Kronevalutamarkedet kan absorbere store virksomhedshandler; The foreign exchange market for kroner is able to absorb large company acquisitions - Asger Munch Grønlund; Lars Risbjerg; Mathias Busk Tjørnum (Danmarks Nationalbank, 2021)
– In the recent years Danish companies have increasingly acquired foreign companies and vice versa. The size of some company acquisitions surpasses the daily turnover in the foreign exchange market for kroner. A case study in this Economic Memo shows that large company acquisitions have not exacerbated krone exchange rate movements over and above the normal daily variation.
Keywords: 330; Capital flows and direct investments; The money and currency markets; Fixed-exchange-rate policy